Does Earnings Management Practice Increase Stock Return? - Nico Alexander; Silvy Christina (TIJAB (The International Journal of Applied Business), 2022)
This research aims to get empirical evidence the effect of earnings management in increasing stock return received by investor. Earnings management is an activity to manipulated financial statement. Earnings management can be used to improve company performance when the company has a bad performance or it can be used to maintain company performance. There are 2 earnings management, accrual and real activity manipulation. This research used both to see which one can increase stock return. This research used multiple regression analysis to test the hypothesis and the samples are manufacturing companies listed on Indonesia Stock Exchange from 2017-2019. 86 companies are selected as samples using purposive sampling. The results showed that earnings management is a negative signal for investors. When a negative signal given to investors, it will cause a decrease in stock return received by investor. This research provides an overview of earnings management practice can make investor suffer losses, so that capital market supervisors can increase the monitoring of this manipulation practices.